2019
DOI: 10.20473/ijar.v1i12019.26-31
|View full text |Cite
|
Sign up to set email alerts
|

Duration Of Ventilation Support Usage And Development Of Ventilator-Associated Pneumonia: When Is The Most Time At Risk?

Abstract: Introduction: Ventilator Associated pneumonia (VAP) is pneumonia that occurs in patients who have been mechanically ventilated for a duration of more than 48 hours. The duration of ventilator use was identified as a risk factor which is trigger of VAP. Objective: This study aimed to determine the association between the duration of ventilator use and the incidence of VAP in patients in the Intensive Care Unit of Dr. Mohammad Hoesin General Hospital, Palembang. Method and Material:This study was an observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…T he use of invasive medical devices to monitor or to support the patient life such as a mechanical ventilator, has increased patient vulnerability to nosocomial infections [ 1 ]. The hospital-acquired infection has been associated with an increased rate of morbidity, mortality, and prolonged hospital stay [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T he use of invasive medical devices to monitor or to support the patient life such as a mechanical ventilator, has increased patient vulnerability to nosocomial infections [ 1 ]. The hospital-acquired infection has been associated with an increased rate of morbidity, mortality, and prolonged hospital stay [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia approximately occurs in 5–10 out of 1000 hospitalized patients, and the number increases by 6–20 times among those receiving mechanical ventilation [ 1 , 5 ]. A study reported a 5–67% incidence of ventilator-associated pneumonia (VAP) cases, and the incidence vary based on the country, setting, and diagnostic approach employed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, Pplat can never be more than the peak inspiratory pressure (PIP), because there will always be an intrinsic resistance that the resistance P must overcome. In mechanical ventilation, this number reflects the positive pressure in centimeters of water pressure (cm H2O) [9] [10]. The normal peak inspiratory pressure (PIP) is 25-30 cm H2O.…”
Section: Introductionmentioning
confidence: 99%
“…ICU Ventilator is a mechanical device used to replace and support respiratory function, this tool is widely used for patient care in the Intensive Care Unit. (ICU) [2]. Research related to ICU ventilators is increasingly being carried out, both hardware development and control system development.…”
Section: Introductionmentioning
confidence: 99%
“…Research related to ICU ventilators is increasingly being carried out, both hardware development and control system development. Ricky Indra [2] measures the duration of ventilator use in patients with pneumonia who require oxygen supply. The need for oxygen also needs to be regulated.…”
Section: Introductionmentioning
confidence: 99%